Pseudotype-Based Neutralization Assays for Influenza: A Systematic Analysis - Carnell, George William; Ferrara, Francesca; Grehan, Keith; Thompson, Craig Peter; Temperton, Nigel James (Frontiers in Immunology, 2015)
The use of vaccination against the influenza virus remains the most effective method of mitigating the significant morbidity and mortality caused by this virus. Antibodies elicited by currently licensed influenza vaccines are predominantly hemagglutination-inhibition (HI)-competent antibodies that target the globular head of HA thus inhibiting influenza virus entry into target cells. These antibodies predominantly confer homosubtypic/strain specific protection and only rarely confer heterosubtypic protection. However, recent academia or pharma-led R&D towards the production of a "universal vaccine" has centered on the elicitation of antibodies directed against the stalk of the influenza HA that has been shown to confer broad protection across a range of different subtypes (H1 to H16). The accurate and sensitive measurement of antibody responses elicited by these "next-generation" influenza vaccines is however hampered by the lack of sensitivity of the traditional influenza serological assays hemagglutinin inhibition (HI), single radial hemolysis (SRH) and microneutralization (MN). Assays utilizing pseudotypes, chimeric viruses bearing influenza glycoproteins, have been shown to be highly efficient for the measurement of homosubtypic and heterosubtypic broadly-neutralizing antibodies, making them ideal serological tools for the study of cross-protective responses against multiple influenza subtypes with pandemic potential. In this review, we will analyze and compare literature involving the production of influenza pseudotypes with particular emphasis on their use in serum antibody neutralization assays. This will enable us to establish the parameters required for optimization and propose a consensus protocol to be employed for the further deployment of these assays in influenza vaccine immunogenicity studies.